Tinjauan Literatur Sistematis: Pengaruh Lingkungan Sosial dan Perlakuan yang Diterima Remaja dari Lingkungan Sosialnya terhadap Psychological Well-Being - Sahening Dian Ardini; Rini Sugiarti; Erwin Erlangga (Syntax Corporation Indonesia, 2024)
This study examines the influence of the social environment and the treatment that adolescents receive from their social environment on psychological well-being. Psychological well-being is a concept that refers to a person's feelings towards the activities of daily life, which includes six main dimensions. This study uses the literature study method (SLR) to collect and analyze data from various sources. The results of the study are expected to provide a deep understanding of the dynamics of these external factors and their impact on the psychological well-being of adolescents. In addition, the study also aims to identify strategies and interventions that can be used by parents, educators, and the community to support the psychological well-being of adolescents, by reducing the negative effects of bullying and implementing more positive and supportive parenting styles.